2022
DOI: 10.3389/fonc.2021.794862
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Geriatric Nutritional Risk Index in Non-Small Cell Lung Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundNovel evidence showed that the Geriatric Nutritional Risk Index (GNRI) may lead to poor prognosis of human cancers. Therefore, we conducted a meta-analysis to explore the impact of GNRI in lung cancer and its prognostic value.MethodsWe searched the databases of PubMed, Web of Science, Embase, Scopus, and Cochrane Library up to July 2021 for relevant research and merged the hazard ratios (HRs) and 95% confidence intervals (CIs) to evaluate the association between GNRI and overall survival (OS), cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Better survival outcomes in patients with higher GNRIs have been reported in various types of solid tumors (e.g., lung cancer, hepatoma, esophageal cancer, kidney cancer, prostate cancer, and diffuse large B-cell lymphoma) [8,20]. However, the underlying mechanism that enables GNRI to determine survival outcomes has not been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Better survival outcomes in patients with higher GNRIs have been reported in various types of solid tumors (e.g., lung cancer, hepatoma, esophageal cancer, kidney cancer, prostate cancer, and diffuse large B-cell lymphoma) [8,20]. However, the underlying mechanism that enables GNRI to determine survival outcomes has not been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This is necessary because the course and the treatment of the malignancy could be very different in patients with different cancers, which may cause significant heterogeneity. During the preparation of our manuscript, two mea-analyses regarding the association between GNRI and outcomes of patients with lung cancer were published [ 43,44]. One study included eight retrospective cohort studies in NSCLC patients and showed that GNRI may be a prognostic factor of NSCLC [43].…”
Section: Discussionmentioning
confidence: 99%
“…During the preparation of our manuscript, two mea-analyses regarding the association between GNRI and outcomes of patients with lung cancer were published [ 43,44]. One study included eight retrospective cohort studies in NSCLC patients and showed that GNRI may be a prognostic factor of NSCLC [43]. However, probably due to the relative number of studies included, no subgroup analyses were performed according to the therapy of the patients (surgery, chemotherapy, or immunotherapy) [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies in oncology showed that GNRI may also be applied as an effective prognostic index in patients with various malignancies, not limited to elderly patients ( 28 ). Indeed, a lower GNRI has been associated with poor prognosis in patients with various malignancies, such as those with esophageal cancer ( 29 ), renal cell carcinomas ( 30 ), and non-small cell lung cancer ( 31 ). However, the influences of GNRI on survival outcomes in patients with CRC, particularly of patients with different cancer stages, remain not comprehensively evaluated.…”
Section: Introductionmentioning
confidence: 99%